A study on balancing career and household: factors influencing women’s work performance / Maizatul Azlin Mokhsin and Nurul Izzati Mohd Salim - Mokhsin, Maizatul Azlin; Mohd Salim, Nurul Izzati (Faculty of Administrative Science and Policy Studies, 2013)
In this study, the researchers focus on the factors influencing women’s work performance at Sekolah Menengah Sains Kuala Selangor. The purpose of the study is to examine the relationships between independent variables toward dependent variable. Besides, the researchers also want to examine which independent variables have high significant relationship with the dependent variables. For this study, the researchers use the simple random technique. The total population was 80 respondents and the selected respondents was 76 in Sekolah Menengah Sains Kuala Selangor. Based on Morgan and Krejcie table, the proposed respondents are 66 respondents. The study conducted had used several methods such as reliabilibity test, normality test, the Pearson correlation and linear regression. The finding shows that the most significant factor in influencing work performance of dual career woman is responsibilities on work and family, followed by occupational choice and lastly is career advancement. Based on the research findings, all the factors have a positive relationship and can influence the work performance of dual career women in Sekolah Menengah Sains Kuala Selangor.